Immunotherapy resistance in esophageal cancer: Possible mechanisms and clinical implications - Fang, Pinhao; Zhou, Jianfeng; Liang, Zhiwen; Yang, Yushang; Luan, Siyuan; Xiao, Xin; Li, Xiaokun; Zhang, Hanlu; Shang, Qixin; Zeng, Xiaoxi; Yuan, Yong (Frontiers in Immunology, 2022)
Esophageal cancer (EC) is a common malignant gastrointestinal (GI) cancer in adults. Though technology in surgical combined with neoadjuvant chemoradiotherapy had advanced rapidly, patients with EC often diagnosed at the advanced stage and five-year survival rate remains unsatisfactory. The poor prognosis and high mortality in EC patients indicate that an effective and validate therapy is of great necessity in EC remedy. Immunotherapy in recent years had been successfully utilized in clinic as novel therapy to treat solid tumor which had bring new hope to cancer patients. Several immunotherapies like checkpoint inhibitors (ICIs), chimeric antigen receptor T cell therapy and tumor vaccines et al. had made significant breakthroughs in EC. However, the overall response rate (ORR) of immunotherapy in EC patients is lower than 30% and most patients who were initially treated with immunotherapy are likely to develop acquired resistance (AR) over time. Immunosuppression had greatly weakened the durability and efficiency of immunotherapies. Because of the heterogeneity among the immune microenvironment and the oncological characteristics highly disparate in different EC individual, the exact mechanism of immunotherapy resistance in EC remains elusive. In this review, we conduct an overview in immunotherapy resistance in EC mainly focus on the terms of current immunotherapies, potential molecular mechanisms underlying the immunosuppression and drug resistance in immunotherapy. Meanwhile, we also discuss prospective biomarkers and novel methods enhancing the effect of immunotherapy to provide a clear insight into EC immunotherapy.